Pertumbuhan Stek Batang Sirih Merah dalam Media Tanam dan dengan Fitohormon Alami - Nila Alvionita M.; Syamsia; Hamzah (Jurnal Galung Tropika, 2026)
Red betel (Piper crocatum Ruiz & Pav.) can be propagated using stem cuttings, but cutting success is affected by planting media and phytohormone application. This study aimed to determine the effects of planting media composition and natural phytohormone type on the growth of red betel stem cuttings. The experiment was arranged in a randomized block design with two factors. The first factor was planting media composition, consisting of husk charcoal and sand at ratios of 1:1, 1:2, and 2:1. The second factor was phytohormone type, consisting of a control, shallot extract, aloe vera extract, and bean sprout extract. The observed variables were cutting success percentage, days to shoot emergence, plant length, shoot length, root length, and number of leaves. The results showed that the interaction between planting media composition and phytohormone type had no significant effect on all observed variables. However, the husk charcoal and sand medium at a ratio of 2:1 tended to produce better growth, with cutting success reaching 100% in several phytohormone treatments, root length reaching 7.00 cm, plant length reaching 18.53 cm, and shoot emergence occurring as early as 32 days after planting. Among the phytohormones, aloe vera extract tended to improve cutting success, shoot length, and number of leaves compared with the other treatments. These findings indicate that a planting medium with a higher proportion of husk charcoal, combined with natural phytohormones, particularly aloe vera extract, has potential to support the early growth of red betel stem cuttings.